BEHAVIOR OF ANOXIC WATER IN THE BANGPAKONG ESTUARY - Morimoto, Akihiko (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2012)
We carried out hydrographic observations in the Bangpakong estuary during transient period from rainy season to dry season in 2011 and 2012. The main objective of the hydrographic observations was to elucidate the behavior of anoxic water mass in the Bangpakong estuary, which was the possible cause of mass mortality of cultured shellfishes in the study area. We had succeeded the CTD and mooring observations in both years, and we had obtained timeâ??series data of DO, salinity, and current velocity for approximately 2 months, which were the first long-term continuous records in terms of water quality in the Bangpakong estuary. From mooring data, it was revealed that DO and salinity at the bottom layer in aquaculture area oscillated with large amplitude, and the period of the oscillation corresponded to tidal variation. Amplitude of the oscillation was large in September and became small in October, and anoxic condition lasted for several days in October in 2011 and 2012. Current direction at station M1 in 2011 was opposite to that of in 2012 throughout the mooring period southward in 2011 and northward in 2012. Wind conditions in Chonburi in both years were almost the same, but river discharge in 2011 was much higer than that of in 2012. Therefore, it was possible that the difference of current direction at station M1 occurred due to change of buoyancy flux, and persistent period of anoxic condition was different between 2 observed years associated with circulation change. It was suggested that mass mortality of cultured shellfishes in Bangpakong estuary was caused by anoxic water because timing of mass mortality corresponded to that of anoxic water appearance qualitatively. It was also suggested that the anoxic water mass in aquaculture area was transported from off shore area by residual currents.